Gambaran Praktik Membuang Masker Pada Mahasiswa Fakultas Kesehatan dan Non-Kesehatan di Kota Semarang - Shifanandita, Novelly; Udijono, Ari; Fauzi, Muh.; Kusariana, Nissa (Jurnal Kesehatan Masyarakat, 2024)
Background: Mask usage has been determined as the main, most effective preventive measure for COVID-19 during the pandemic to limit viral transmission. The obligation of regular mask usage and replacement from health protocols across the globe has really affected the rise of mask waste in the environment. However, the waste of used mask more often than not, found in places they don’t belong. This phenomenon is connected to public awareness and how they implement good health practice on daily basis. Mask waste are also found often near where the university students live, even though they were expected to be the pillars of the public eye in terms of giving good examples regarding public health practices and measures. The objective of this research is to describe the differences found in health practices among health students in university and other students that don’t come from health faculties.Methods: Cross-sectional design was used for this descriptive, quantitative research, with simple random sampling as the sampling technique, where all university students in Semarang have the same chance to be chosen as the respondents, obtaining 333 in total.Result: According to bivariate analysis conducted, good practice on handling mask waste is found more among the health students (65,6%) compared to non-health students. On the contrary, bad practice on handling mask waste is found more among the non-health students (56,9%) compared to health students.Conclusion: Good practice on handling mask waste has been implemented well by most of the health students compared to the non-health students, whereas bad practice on handling mask waste is still found more among the non-health students compared to the health students.